2020
DOI: 10.1111/sltb.12683
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the interpersonal theory of suicide in the context of attention‐deficit/hyperactivity disorder symptomatology and suicide ideation

Abstract: Objective The current study examines components of the Interpersonal Theory of Suicide as mediators of the association between attention‐deficit/hyperactivity disorder (ADHD) symptoms and suicide ideation in college students with elevated depressive symptoms. Specifically, indirect effects of perceived burdensomeness and thwarted belongingness were simultaneously evaluated on the association between self‐reported ADHD symptoms and suicide ideation, controlling for gender and levels of depression. Method Partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
1
2
1
Order By: Relevance
“…74 A single study in the general population examined this association in relation to the ITS, showing that the association between ADHD traits and suicide ideation was indeed mediated by higher scores in thwarted belongingness and perceived burdensomeness. 41 While the present study supports a mediating role for perceived burdensomeness, the apparent irrelevance of thwarted belongingness stands in contrast to these previous findings and those of Pelton et al, 32 who previously found associations between this constructs and both suicide ideation and attempts. Notedly, as those authors did not control for depression, the effect of thwarted belongingness they observed could have been confounded by depression.…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…74 A single study in the general population examined this association in relation to the ITS, showing that the association between ADHD traits and suicide ideation was indeed mediated by higher scores in thwarted belongingness and perceived burdensomeness. 41 While the present study supports a mediating role for perceived burdensomeness, the apparent irrelevance of thwarted belongingness stands in contrast to these previous findings and those of Pelton et al, 32 who previously found associations between this constructs and both suicide ideation and attempts. Notedly, as those authors did not control for depression, the effect of thwarted belongingness they observed could have been confounded by depression.…”
Section: Discussioncontrasting
confidence: 93%
“…Our first analyses focused on thwarted belongingness and perceived burdensomeness, which we hypothesised might occur at higher levels in autistic people with ADHD due to the deleterious academic, occupational, social and emotional correlates of co-occurring autism and ADHD. 46,63,64 In the general public, the association between these constructs and ADHD features mediated their association with suicide ideation, 41 consistent with the assertions of the ITS. We hypothesised a similar mediating role of these constructs between co-occurring ADHD and suicide ideation in our autistic sample, but given that thwarted belongingness and perceived burdensomeness may be relevant to suicide attempts in autistic people, 32 we also examined their role in the association between co-occurring ADHD and suicide attempts.…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…Guilt appears to lead instantly to emotional excess and, over time, to a maladaptive self-scheme. 37 It appears that the burden of guilt causes youngsters to turn inside and reluctant to seek assistance from others. 38 Despair appears to be associated with a lack of purpose and a lack of a reason to live, both of which contribute to the belief that suicide is a reasonable option because life lasts longand will never improve.…”
Section: Discussionmentioning
confidence: 99%